Pelatihan Red Hat OpenShift Development Introduction to Containers with Podman Untuk Mahasiswa Universitas Mikroskil - R. A. Fattah Andriansyah; Nurhayati; Arisman Arisman (Educativo: Jurnal Pendidikan, 2023)
In line with the development of information technology and communication, Mikroskil University always make efforts to prepare students in order to contribute at Industrial revolution 4.0. One of them has to understand and practice Linux based on networking skill using Red Hat with Podman container engine. Today software development is increasingly using an approach called containerization, where software standard packages known as containers combine application code together with configuration files and associated libraries and with the dependencies needed for applications to run. Analogies such as the shipping industry using physical containers to isolate various cargoes for transport by ship and rail. This enables developers and IT professionals to deploy applications seamlessly across environments with Comparing Containers to Virtual Machines, such as Container virtual machines (VMs), Kubernetes and Red Hat OpenShift Container Platform (RHOCP).